Tapering of Biological Agents in Juvenile ERA Patients in Daily Clinical Practice - Liao, Chun-Hua; Chiang, Bor-Luen; Yang, Yao-Hsu (Frontiers in Medicine, 2021)
Objectives: We aim to evaluate the proportion and characteristics of enthesitis-related arthritis (ERA) patients in whom medications can be withdrawn in daily practice and to analyze the factors associated with flare-ups during medication tapering of these patients. Methods: We retrospectively reviewed records of patients under 16 years old diagnosed with ERA from April 2001 to March 2020 in one tertiary medical center in Taiwan. Patients were categorized by different medication uses: conventional disease modifying anti-rheumatic drugs (cDMARDs) only and cDMARDs plus biologics. Demographics, laboratory data, presence of uveitis, and medication withdrawal rate were analyzed. Subgroup analysis was performed in the patients with cDMARDs plus biologics to identify factors associated with flare-ups during medication tapering of these patients. Statistical analysis was performed using R (v3.6.0) Results: There were 75 juvenile ERA patients with a median onset age of 10.28 years old. Nineteen (25.3%) patients used cDMARDs for disease control; 56 (74.7%) patients depended on cDMARDs plus biologics. Poly-articular involvement was noted in 29 (38.7%) patients, and it occurred more frequently in the cDMARDs plus biologics subgroup (cDMARDs only, 5.3%; cDMARDs plus biologics, 53.6%; P =0.0001). ANA positivity was observed in 18 (24.0%) patients, and it occurred more frequently in the cDMARDs plus biologics subgroup (cDMARDs, 0%; cDMARDs plus biologics, 32.1%; P =0.0038). The overall medication withdrawal rate was 34.7%, and it occurred more frequently in patients with cDMARDs only (cDMARDs only, 84.2%; cDMARDs plus biologics, 17.9%; P <0.001). In the subgroup analysis of patients with cDMARDs plus biologics, patients on biologics tapering with flare-up had a significantly longer time interval between disease onset and initiation of cDMARDs (biologics tapering without flare-up: 0.27 (0.11-0.73) years; biologics tapering with flare-up: 1.14 (0.39-2.02) years; ever withdrawing biologics: 0.26 (0.18-0.42) years, P=0.0104). Conclusion: Juvenile ERA patients with polyarticular involvement had a higher risk of developing cDMARDs refractory and progressing to biologics use. Patients with a long time interval between disease onset and initiation of cDMARDs were prone to experience flare-up during tapering of biologics.